Bring back order in the polymethine dye medley: Classification, structure and spectra. (December 2022) - Mustroph, Heinz
Abstract: The term polymethine dyes was introduced by Walter König in 1922 and four years later he created a general classification of polymethine dyes. In current terms polymethine dyes are characterized by a conjugated chain of (2 n  + 1) sp 2 -hybridized carbon atoms that connects a terminal π -electron accepting group and a terminal π -electron donating group. The second feature is an odd number 2 n + 3 of π -centres and an even number 2 n + 4 of π -electrons, where n is equal to the number of –C(R) = C(R′)– groups (usually vinylene groups –CHCH–). These features confer special structure-absorption relationships on the class owing to their strong influence over the nature of possible transitions from the electronic ground state and thus dye absorption spectra. Over the years, the general definition has been divided into sub-classes - in some instances, not systematically - with a great diversity of complete different chemical structures, belonging to the polymethine dyes. Some of these aspects have been forgotten or overlooked or even misunderstood and such mistakes have been propagated in the literature. In this review an attempt is made to bring clarity to the nomenclature of dye sub-classes, the history of the respective terms and to highlight common structural features. Graphical abstract: The first synthesized polymethine dyes were colorants of beautiful cyan color. Since many different new dye classes were prepared and used in a wide variety of industrial applications. A lot of them belong to the polymethine dye class due to their special π -electronic features. In this review an attempt is made to bring clarity to the nomenclature of dye sub-classes, the history of the respective terms and to highlight common structural features. Image 1 Highlights: Many different dye classes belong to the polymethine dye class due to their special p -electronic features. This article attempts to bring clarity to the names of the individual polymethine dye classes. In addition, it attempts to highlight common p-electronic features and to discuss the associated typical properties.